Tipologi Fatwa Ulama dalam Khazanah Keislaman - Muchtar, Nurkhalis (Serambi Tarbawi, 2024)
Fatwa is the process of providing answers to problems that arise or questions that arise. The need of the people for fatwas has been felt since the beginning of the development of Islam. In Islam, fatwa has a high position so not everyone can give fatwa. Fatwas that come from non-experts will cause fatal errors to arise in society. Islamic scholars have written their thoughts regarding the procedures for giving fatwa in many works. However, as far as we have read, we have not found any work that examines the typology of ulama in giving fatwa, especially through their written works contained in Islamic treasures. On the other hand, there is also the emergence of wrong paradigms in giving fatwa, some are too rigid and some are too flexible in giving fatwa. This research uses a qualitative descriptive research method on library data findings, with a library research and content analysis approach, it is concluded that the ulama in giving fatwas have different typologies in giving fatwas. This research also reveals that there are many fatwa books by ulama with different fatwa typologies. By knowing the typology of ulama in giving fatwas, it is hoped that this will be a way to understand the differences in fatwas, so that stability and peace can be created in the existing diversity.